The analysis of the level of nurses’ conscious about the professional autonomy - Glińska, Jolanta; Nowak, Anna; Brosowska, Beata; Lewandowska, Małgorzata (Nursing Problems / Problemy Pielęgniarstwa, 2010)
Introduction. Nowadays it is expected high qualifications, competences and professionalism from the nurses. According the act from the day 5 July 1996 about nurse and midwifery profession “nurse and midwifery profession are independent”. Nowadays in the autonomy times the nurse is seen not by the prism of the physician’s orders and instructions but as the person working with a patient and with a doctor not for him. The nursing care subject who is a patient must be the most important thing in the center of nurses focus always in all nurses actions. The nurse must be the patients’ co-partner, teacher and spokesmen. On area of century together with the development of medical and social sciences the roles and tasks which were fulfilled by people executing the care actions were changing. The nursing was evaluating from spontaneous care on the patients which was fulfilled because of hart and philanthropic motive to professional execution of the job. Now we have professional actions which are organized and based on the legal norms. Aim. The estimation of the level of the nurses’ knowledge on the professional autonomy. Material and method. Research were conducted in 2008 among 200 nurses working in outpatient clinic and hospitals within Łódź. Getting results were analysis by non parametric tests chi2 Pearson. Results and conclusions. There has recognized the low level of the nurses’ aware concerning the autonomy and independency of nurses profession. From our researche comes from the level of the nurses’ aware was increasing together with the level of their education and shorter period of the seniority. It has found out the statistical correlation on the level of p < 0.001. There has recognized the low level of the nurses’ knowledge on the nursing professional functions. It has shown the statistical correlation between the level of the education and the level of the knowledge on the nursing functions (p 0.05) from the seniotity. Nursing Topics 2010; 18 (4): 477-482